Development Of Risk-Based Audit Method Standard For Stadium Project Using Design And Build Contract To Minimize Dispute Based On Inspectorate Perpective - Ferdinand, Joshua; Putro, Anggoro; Latief, Yusuf (International Journal of Science, Technology & Management, 2023)
Construction projects have been developing from the management side year by year. One of the problems that government has been facing government construction projects over the years is the duration of the procurement process that takes too long which is hard to be implemented if the project is urgent in terms of time. This creates the urgency to seek the solutions to the problem of how to shorten the time of the procurement process. The design and build integrated contract method that unites the planning and implementation process simultaneously is able to answer these problems and shorten the procurement time of government construction projects. However, there are many disputes faced by construction projects that use integrated design contracts postproject, one of which comes from the Government Internal Supervisory Apparatus (APIP) or commonly called the Inspectorate. This is because there are several different standard between the inspectorate and the owner or contractor that has been used in the process of government construction projects Audit. This study aims to identify the standards of the audit process of the Inspectorate, analyze the risks that cause disputes, and to develop standards for risk-based audit methods for design and build-based construction projects in order to minimize disputes that occured from the inspectorate side of perspective.